2023
DOI: 10.1172/jci.insight.161810
|View full text |Cite
|
Sign up to set email alerts
|

An RPS19-edited model for Diamond-Blackfan anemia reveals TP53-dependent impairment of hematopoietic stem cell activity

Abstract: Diamond-Blackfan anemia (DBA) is a genetic blood disease caused by heterozygous loss-offunction mutations in ribosomal protein (RP) genes, most commonly RPS19. The signature feature of DBA is hypoplastic anemia occurring in infants, although some older patients develop multi-lineage cytopenias with bone marrow hypocellularity. The mechanism of anemia in DBA is not fully understood and even less is known about the pancytopenia that occurs later in life, in part because patient hematopoietic stem and progenitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
1
7
1
Order By: Relevance
“…Majority of the patients in this study received a melphalan-based RIC therapy ( 45 ). This is consistent with laboratory observations where wildtype hematopoietic stem/progenitor cells had a competitive advantage over RPS19 haploinsufficient cells in mouse and human cell models of DBA, providing rationale for use of RIC regimens ( 18 , 59 ). Moreover, in the context of poor outcomes in older patients with DBA, use of RIC therapy could potentially be an attractive option for this patient population ( 27 ).…”
Section: Transplant Indications and Outcomessupporting
confidence: 88%
See 3 more Smart Citations
“…Majority of the patients in this study received a melphalan-based RIC therapy ( 45 ). This is consistent with laboratory observations where wildtype hematopoietic stem/progenitor cells had a competitive advantage over RPS19 haploinsufficient cells in mouse and human cell models of DBA, providing rationale for use of RIC regimens ( 18 , 59 ). Moreover, in the context of poor outcomes in older patients with DBA, use of RIC therapy could potentially be an attractive option for this patient population ( 27 ).…”
Section: Transplant Indications and Outcomessupporting
confidence: 88%
“…In addition to a specific erythroid failure seen in younger patients, bone marrow hypocellularity, progressive multilineage cytopenias and immunodeficiency are noted in older patients with DBA, suggesting impairment of hematopoietic stem and progenitor cells (HSPCs) ( 15 17 ). Mechanisms of DBA HSPCs dysfunction are not clear, although TP53 activation appears to play a critical role ( 18 ). Additionally, systematic review of published case reports suggested an increased risk of cancer in DBA, which was subsequently confirmed by pioneering studies lead by the DBA Registry of North America (DBAR) ( 19 21 ).…”
Section: Pathophysiology and Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking advantage of the efficiency of CRISPR/Cas9 editing of RPS19 , the authors knocked in a GFP reporter to the RPS19 locus, enabling tracking of RPS19 disrupted clones by the presence of the GFP signal. They found significant cellular toxicity related to ribonucleoprotein delivery of CRISPR/Cas9 components, unlike what was recently described in the RPS19 CRISPR model by Bhoopalan et al , 17 perhaps owing to differences in electroporation conditions. Nonetheless, to avoid some of this toxicity, the authors optimized mRNA delivery of CRISPR components by nanostraws and demonstrated the efficacy of this approach in primary human cells for the first time.…”
mentioning
confidence: 64%